#TITLE_ALTERNATIVE# - BUDIANTO (NIM : 101 06 101); Pembimbing Tugas Akhir : Dumaria R. Tampubolon, Ph.D., INDRAWAN
One of the important quantities in determining the price of an insurance product is the risk premium. The risk premium is a premium which is determined from the distribution of the aggregate loss. The data used in this skripsi is the claims data of the automobile insurance industries in Indonesia for underwriting year 2007. The process in determining appropriate models for the number and amount of claims consist of four steps: cleaning the data; …tting appropriate models; estimating the parameters of the models; and testing the goodness of the models …tted. Two methods are used to determine the probability function of the aggregate loss: recursive method and simulation. The recursive method determines the probability of the aggregate loss at discrete points. From the simulation, the mean, variance and percentiles of the aggregate loss may be determined. It is found that the mean and variance of the aggregate loss obtained theoretically and by simulation are similar.